Dual-Modality Surface-Enhanced Resonance Raman Scattering and Multispectral Optoacoustic Tomography Nanoparticle Approach for Brain Tumor Delineation - Neuschmelting, Volker; Harmsen, Stefan; Beziere, Nicolas; Lockau, Hannah; Hsu, Hsiao-Ting; Huang, Ruimin; Razansky, Daniel; Ntziachristos, Vasilis; Kircher, Moritz F. (Small, 2018)
Difficulty in visualizing glioma margins intraoperatively remains a major issue in the achievement of gross total tumor resection and, thus, better clinical outcome of glioblastoma (GBM) patients. Here, the potential of a new combined optical + optoacoustic imaging method for intraoperative brain tumor delineation is investigated. A strategy using a newly developed gold nanostar synthesis method, Raman reporter chemistry, and silication method to produce dual-modality contrast agents for combined surface-enhanced resonance Raman scattering (SERRS) and multispectral optoacoustic tomography (MSOT) imaging is devised. Following intravenous injection of the SERRS-MSOT-nanostars in brain tumor bearing mice, sequential MSOT imaging is performed in vivo and followed by Raman imaging. MSOT is able to accurately depict GBMs three-dimensionally with high specificity. The MSOT signal is found to correlate well with the SERRS images. Because SERRS enables uniquely sensitive high-resolution surface detection, it could represent an ideal complementary imaging modality to MSOT, which enables real-time, deep tissue imaging in 3D. This dual-modality SERRS-MSOT-nanostar contrast agent reported here is shown to enable high precision depiction of the extent of infiltrating GBMs by Raman- and MSOT imaging in a clinically relevant murine GBM model and could pave new ways for improved image-guided resection of brain tumors.
CRIS-Team Scopus Importer:2023-03-08
Keywords: glioblastoma; multispectral optoacoustic tomography (MSOT); nanomedicine; neurooncology; photoacoustic imaging; surface-enhanced resonance Raman spectroscopy (SERRS)